LEGAL PROTECTION FOR THE COMMUNITY IN RESOLUTION OF LAND DISPUTES - Mahardika, Dekha Isvan; Suprapto (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
This study discusses the resolution of land disputes, which are a complex and ongoing problem in Indonesia, especially when community rights to land conflict with state or corporate interests. This problem often leads to injustice, criminalization, and even human rights violations, especially against vulnerable groups such as farmers and indigenous peoples. This study aims to analyze the forms of legal protection provided to communities in resolving land disputes and evaluate the legal mechanisms available under the Indonesian legal system. Legal protection for communities has been regulated in various regulations, such as the Basic Agrarian Law (UUPA), the Human Rights Law, and the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (BPN). However, its implementation still faces serious challenges, particularly in terms of accessibility, bias by officials, and transparency. Meanwhile, dispute resolution mechanisms are divided into litigation and non-litigation channels, including mediation by land offices, customary deliberations, and resolution through independent institutions such as the National Commission on Human Rights (Komnas HAM) and the Ombudsman. Unfortunately, the effectiveness of these mechanisms depends heavily on the government's commitment and the capacity of relevant institutions to ensure substantive justice.